ANALISIS ECONOMIC VALUE ADDED (EVA) PADA PT BANK NEGARA INDONESIA TBK - Jilly Karamoy; Dolina L. Tampi; Danny D. S. Mukuan (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract: The purpose of this research is to analyze and determine the financial performance of PT Bank Negara Indonesia Tbk, that are reviewed with economic value added method. Based on the results of research and discussion, can be concluded that PT Bank Negara Indonesia Tbk succeeded in creating a positive economic value added for the company Rp.1,487,357 (in Million Rupiah) in 2013, Rp.2,237,350 (in millions of rupiah) in 2014, and Rp.2,360,665 (in millions Rupiah) in 2015. The management have been working according to the wishes of shareholders, so the shareholders can entrust their investment to the company.Keywords: Economic Value Added